Film, adaptation and cooking with the recipes of julia child, julie powell and nora ephron - Cristian, Réka M. (AMERICANA E-journal of American Studies in Hungary, 2018)
Réka M. Cristian discusses the topics of adaptation and cooking in Nora Ephron’s foodie film Julie and Julia based on Julia Child’s Mastering the Art of French Cooking that had a profound impact on several aspects of post-World War II American vernacular culture and Julie Powell’s novel Julie and Julia: 365 Days, 524 Recipes, 1 Tiny Apartment Kitchen which was based on the author’s blog documenting a year of cooking all Child’s recipes. The article focuses on the issue of intertextual dialogism and refunctioning as primary means of adaptation and also on the issue of microhistorical event(s) and stardom involved in the making of Ephron’s film.